Legal Protection for Trademark Rights Holders according to Indonesian Law - Muhamat Farera Syahbria Hutama; Moh. Indra Bangsawan (Universitas Muhammadiyah Surakarta, 2023)
Basically, humans must always use their minds to think, because thinking is an activity that humans cannot avoid in life. Humans have different intellectual capacities to process their thoughts, and those thoughts create things in the form of ideas or ideas and imagination. This form of idea or concept is then called Intellectual Property Rights (IPR). A trademark is part of Intellectual Property Rights which cannot be separated from the meaning that trademark rights originate from discoveries in other parts of Intellectual Property Rights, for example copyright. In a brand there are several parts of the creation, such as the logo or letter design. For manufacturers, a brand is a representation and good name for the company, nothing more than an element of business strategy. This writing article also applies normative juridical writing methods by researching library materials, namely primary and secondary legal materials. The data collection technique uses library research, by collecting data and information or legal materials related to the substance of the research. After the legal material has been collected, an analysis is carried out and a suitable core is drawn from the problems contained in the problem formulation. This writing also applies data analysis techniques through deductive logic. The trademark registration system in Indonesia based on the MIG Law follows a constitutional system on the